2017
DOI: 10.4317/jced.54127
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nicotine on machined- and anodized-surface implants. Histometric analysis

Abstract: BackgroundThe nicotine may generate a influence on bone repair and longevity of dental implants. This fact makes studies to improve the surface of the implants are constantly conducted. This study aimed to evaluate the influence of subcutaneous nicotine injection in the osseointegration process on different implant surfaces, through histomorphometric analysis.Material and MethodsTherefore, twenty-two male rabbits were randomly distributed into two groups according to the subcutaneous injections: (1) nicotine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The reverse torque removal values are directly related to the contact bone/ implant interface, bone density, quantity of cortical bone around the torque after certain periods. There was no significant differences between the torques induced by machined and anodized surfaces of test groups in the present experiment, which is in agreement with others reports [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Likewise, no difference was observed in the control groups.…”
Section: ■ Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The reverse torque removal values are directly related to the contact bone/ implant interface, bone density, quantity of cortical bone around the torque after certain periods. There was no significant differences between the torques induced by machined and anodized surfaces of test groups in the present experiment, which is in agreement with others reports [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Likewise, no difference was observed in the control groups.…”
Section: ■ Discussionsupporting
confidence: 83%
“…The results showed that low nicotine dose administration did not cause deleterious effects on bone healing and implant osseointegration, which is in agreement with other study [14][15] . Cotinine levels observed in the rabbits after the daily doses of nicotine were equivalent to concentrations observed in light smokers (less than 10 ng/mL) [16][17] , which did not, reproduced the negative impact of cigarette around titanium implants. According to Cesar-Neto et al 18 subcutaneous administration of nicotine (3 mg/kg) three times a day, did not influence healing around implants.…”
Section: ■ Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Porous surfaces may also improve bony ongrowth in patients with osteoporosis or in those who smoke. 15,16 Titanium plasma sprays typically create surfaces with low interconnectivity and small pore sizes (100-150 μm). In addition, the porous surface depth can vary significantly secondary to the manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…The osseointegration process is defined as the direct contact of living bone and a loaded implant at the microscopic level [1]. This event has been shown by different animal models [24] and in a few human histological reports [5], being influenced by many variable like systemic conditions (diabetes mellitus [3] and cigarette smoking [4]), implant surface macro- and microtexture (roughness and treatment methods) [6, 7], and prosthetic restoration stability [8].…”
Section: Introductionmentioning
confidence: 99%